Composite carbon source induced positive electrode material, preparation method, positive plate and application

Through the preparation method of positive electrode material induced by composite carbon source, the problem of low electronic conductivity of the positive electrode material of sodium ion battery is solved, and high-performance and high-purity positive electrode material preparation is achieved, which improves the electrical performance of the battery.

CN119725426APending Publication Date: 2025-03-28HEFEI ZHONGYIN NEW MATERIAL CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411630904.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The electronic conductivity of the existing sodium ion battery cathode materials is limited, and the carbon coating method causes a decrease in energy density, and there is a lack of a green, low-cost, simple large-scale cathode material preparation method.

Method used

The molar ratio is adjusted by using a composite carbon source-induced positive electrode material, including a sodium, a phosphorus, an iron, a first carbon source and a second carbon source, and the positive electrode material is prepared by sanding nano-sanding, spray-drying and sintering treatment.

Benefits of technology

In-situ nitrogen-loaded carbon source coating is achieved, the electronic conductivity and hydrophilicity of the positive electrode material are improved, the purity and crystallinity of the material are improved, and the electrical properties of the electrode sheet are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005135893740000011
    Figure HDA0005135893740000011
  • Figure HDA0005135893740000012
    Figure HDA0005135893740000012
  • Figure HDA0005135893740000021
    Figure HDA0005135893740000021
Patent Text Reader

Abstract

The invention discloses a composite carbon source induced positive electrode material, a preparation method, a positive plate and application, and relates to the technical field of sodium ion batteries. The positive electrode material induced by the composite carbon source is prepared from components including a sodium source, a phosphorus source, an iron source, a first carbon source and a second carbon source, and the dosage of the sodium source, the dosage of the phosphorus source and the dosage of the iron source are adjusted, so that the molar ratio range of sodium, phosphorus and iron is (1-1.05): 1: (0.65-0.85); the total weight of the first carbon source and the second carbon source accounts for 20wt% of the total weight of the sodium source, the phosphorus source and the iron source; wherein the weight ratio of the first carbon source to the second carbon source is (1-20): 1; the second carbon source is a nitrogen-containing organic matter. By adding the second carbon source and introducing the nitrogen-containing organic matter, in-situ nitrogen-loaded carbon source coating is realized, and the electronic conductivity of the positive electrode material can be obviously improved; lone pair electrons of nitrogen atoms and hydrogen atoms of water form hydrogen bonds, so that the hydrophilicity is improved, the uniformity is improved, and the purity and the crystallinity are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of sodium ion batteries, and in particular to positive electrode materials induced by composite carbon sources, preparation methods, positive electrode sheets and applications. Background Art

[0002] People prefer clean renewable energy, such as solar energy, wind energy, and hydropower. However, these renewable energy sources are intermittent and unstable, so the development of reliable energy storage systems is particularly important. Compared with other energy storage methods, electrochemical energy storage is widely used in different industries due to its stability and portability.

[0003] The high energy density and long service life of lithium-ion batteries make them widely used. However, with the rapid development of the electric vehicle market, lithium resources cannot meet the needs of both power batteries and energy storage batteries, and the uneven distribution of lithium resources is an important challenge to our country's energy storage security. Sodium has abundant reserves and price advantages, and has similar physical and chemical properties to lithium. Sodium-ion batteries are considered to be a beneficial supplement to lithium-ion batteries and have broad application prospects in the field of large-scale energy storage.

[0004] In sodium-ion batteries, cathode materials are mainly divided into layered oxides, Prussian blue and its analogs, and polyanion compounds. Among them, iron-based polyanion cathode materials have low cost, excellent cycle life, and great application potential. However, the development of polyanion compounds is limited by their electronic conductivity. Carbon coating is currently the mainstream method to solve electronic conductivity, but too high carbon content will reduce energy density. Therefore, there is an urgent need for a green, low-cost, simple large-scale cathode material and preparation method. Summary of the invention

[0005] In order to solve at least one of the above technical problems and develop a new positive electrode material for sodium ion batteries, the present application provides a composite carbon source-induced positive electrode material, a preparation method, a positive electrode sheet and an application.

[0006] On the one hand, the present application provides a composite carbon source induced positive electrode material, which is prepared from components including a sodium source, a phosphorus source, an iron source, a first carbon source, and a second carbon source. The amounts of the sodium source, the phosphorus source, and the iron source are adjusted so that the molar ratio of sodium, phosphorus, and iron is in the range of 1 to 1.05:1:0.65 to 0.85; the total weight of the first carbon source and the second carbon source accounts for 20wt% of the total weight of the sodium source, the phosphorus source, and the iron source; the weight ratio of the first carbon source to the second carbon source is 1 to 20:1; the second carbon source is a nitrogen-containing organic matter.

[0007] Optionally, the sodium source is one or more of disodium hydrogen phosphate, sodium dihydrogen phosphate, sodium phosphate, sodium carbonate, sodium bicarbonate, sodium pyrophosphate, sodium oxalate, and sodium acetate;

[0008] And / or, the iron source is one or more of ferric nitrate, ferric phosphate, ferrous oxalate, ferric oxide, ferrosiric oxide, ferrous acetate, and ferric acetylacetonate;

[0009] And / or, the phosphorus source is one or more of sodium dihydrogen phosphate, disodium hydrogen phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, sodium phosphate, sodium pyrophosphate, and phosphoric acid;

[0010] and / or, the carbon source is one or more of citric acid, ascorbic acid, oxalic acid, stearic acid, glucose, agarose, sucrose, and cellulose;

[0011] And / or, the second carbon source is one or more of polyethyleneimine, polyacrylamide, polyamide, polyimide, polyurea, polyacrylonitrile, melamine, and diethylenetriaminepentaacetic acid.

[0012] Optionally, the solid content of the composite carbon source-induced positive electrode material provided in the present application is 5 to 50 wt %.

[0013] In a second aspect, the present application provides a method for preparing the above-mentioned positive electrode material, comprising the following steps:

[0014] S1. Weigh the sodium source, phosphorus source, first carbon source, second carbon source and iron source respectively, add them into deionized water in sequence, stir and disperse to obtain a suspension;

[0015] S2, performing sand milling and nano-processing on the suspension prepared in S1, and then spray drying the suspension to obtain a precursor powder;

[0016] S3. The precursor powder prepared in S2 is sintered in an inert atmosphere to obtain a composite carbon source-induced positive electrode material.

[0017] Optionally, in S1, the stirring method is one of mechanical stirring and magnetic stirring; the stirring speed is 100-1200 rpm; the stirring temperature is 10-60° C.; and the stirring time is 1-10 h.

[0018] Optionally, in S2, the sanding speed is 2000 rpm; the sanding temperature is 20° C.; and the D50 of the solid particles after sanding is less than 100 nm.

[0019] Optionally, in S2, the inlet temperature of the spray drying is 260°C, the outlet temperature is 110°C, the fan speed is 90%, and the peristaltic pump speed is 40%.

[0020] Optionally, in S3, the inert atmosphere is one of argon, nitrogen, and a hydrogen-argon mixed gas.

[0021] Optionally, in S3, the sintering temperature is 500-600°C, the heating rate is 1-5°C / min, and the sintering time is 10-15h.

[0022] In a third aspect, the present application provides an electrode sheet prepared from a positive electrode material induced by the above-mentioned composite carbon source.

[0023] In a fourth aspect, the present application provides the application of the above-mentioned composite carbon source induced positive electrode material in the field of sodium ion batteries.

[0024] In summary, the present invention includes at least one of the following beneficial technical effects:

[0025] 1. The technical solution of this application can significantly improve the electronic conductivity of the positive electrode material by adding a second carbon source and introducing nitrogen-containing organic matter to achieve in-situ nitrogen-loaded carbon source coating;

[0026] 2. By utilizing the lone pair electrons of nitrogen atoms in nitrogen-containing organic matter to form hydrogen bonds with hydrogen atoms in water, the hydrophilicity of the material is improved, the uniformity of the suspension slurry is improved, thereby improving the purity and crystallinity of the material, and further improving the electrical properties of the prepared electrode sheet;

[0027] 3. The preparation method in the technical solution of the present application is simple, and there is no need to carry out process modification on the existing production equipment. Only a small amount of nitrogen-containing carbon source needs to be introduced to prepare high-performance and high-purity phosphoric acid / sodium iron pyrophosphate positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The X-ray diffraction pattern of the positive electrode material prepared in Example 1;

[0029] Figure 2 FESEM images of the positive electrode material prepared in Example 2 at different magnifications;

[0030] Figure 3 The first cycle charge and discharge curve of the sodium ion battery corresponding to the positive electrode material prepared in Example 3;

[0031] Figure 4 The rate test curves of the sodium ion batteries corresponding to the positive electrode materials prepared in Example 4, Example 5 and Comparative Example 1;

[0032] Figure 5 This is a long cycle data diagram of the sodium ion battery corresponding to the positive electrode material prepared in Example 6;

[0033] Figure 6 The first cycle charge and discharge curve of the sodium ion battery corresponding to the positive electrode material prepared in Example 7;

[0034] Figure 7 This is the first cycle charge and discharge curve of the sodium ion battery corresponding to the positive electrode material prepared in Example 8. DETAILED DESCRIPTION

[0035] The present application is further described in detail below with reference to the accompanying drawings and embodiments.

[0036] In the following examples of the present application, the main components involved, unless otherwise specified, are purchased from commercially available products, and the main production methods involved, unless otherwise specified, are large-scale production methods. Specific embodiments

[0038] Example 1

[0039] Weigh 211.457g NaH2PO4, 709.747g FePO4, 249.397g Na2CO3, 100g C6H 10 O8, 5g polyethyleneimine was added to 3L deionized water, stirred for 1h to mix evenly, and then added to a sand mill and sanded for 5h to obtain a precursor suspension;

[0040] The obtained precursor suspension is spray dried to obtain a precursor powder, which is then sintered at 500° C. for 10 h in an inert gas atmosphere to obtain a nitrogen-doped sodium iron phosphate pyrophosphate positive electrode material (i.e., the composite carbon source induced positive electrode material described in the technical solution of the present application), abbreviated as NFPP-N1.

[0041] The positive electrode material prepared in Example 1 was characterized by XRD phase. Figure 1 It can be seen from the XRD spectrum that no other impurity phases were retrieved, indicating that the purity of the prepared sample meets the requirements.

[0042] Example 2

[0043] Weigh 211.457g NaH2PO4, 709.747g FePO4, 249.397g Na2CO3, 100g C6H 10 08, 5g polyacrylamide was dissolved in 3L deionized water, stirred for 1h to mix evenly, and then added to a sand mill and sanded for 5h to obtain a precursor suspension;

[0044] The obtained precursor suspension is spray dried to obtain a precursor powder, which is then sintered at 500°C for 10 hours in an inert gas atmosphere to obtain a nitrogen-doped sodium iron phosphate pyrophosphate positive electrode material (i.e., the composite carbon source induced positive electrode material described in the technical solution of the present application), abbreviated as NFPP-N2.

[0045] The positive electrode material prepared in Example 2 was characterized by FESEM morphology. By introducing a nitrogen-containing carbon source, the complexing effect of the material was enhanced, and the surface morphology of the material was significantly changed. Figure 2 It can be seen that the material synthesized in Example 2 has uniform particle size and a unique ball-and-socket structure, and the material is more tightly combined, thereby improving its rate performance.

[0046] Example 3

[0047] Weigh 211.457g NaH2PO4, 709.747g FePO4, 249.397g Na2CO3, 100g C6H 10 O8, 5g polyamide was added to 3L deionized water, stirred for 1h to mix evenly, and then added to a sand mill and sanded for 5h to obtain a precursor suspension;

[0048] The obtained precursor suspension is spray dried to obtain a precursor powder, which is then sintered at 500°C for 10 hours in an inert gas atmosphere to obtain a nitrogen-doped sodium iron phosphate pyrophosphate positive electrode material (i.e., the composite carbon source induced positive electrode material described in the technical solution of the present application), abbreviated as NFPP-N3.

[0049] Example 4

[0050] Weigh 211.457g NaH2PO4, 709.747g FePO4, 249.397g Na2CO3, 100g C6H 10 O8, 5g polyimide was mixed in 3L deionized water, stirred for 1h to mix evenly, and then added to a sand mill and sanded for 5h to obtain a precursor suspension;

[0051] The obtained precursor suspension is spray dried to obtain a precursor powder, which is then sintered at 500° C. for 10 h in an inert gas atmosphere to obtain a nitrogen-doped sodium iron phosphate pyrophosphate positive electrode material (i.e., the composite carbon source induced positive electrode material described in the technical solution of the present application), abbreviated as NFPP-N4.

[0052] Example 5

[0053] Weigh 211.457g NaH2PO4, 709.747g FePO4, 249.397g Na2CO3, 100g C6H 10 08, 5g polyurea was dissolved in 3L deionized water, stirred for 1h to mix evenly, and then added to a sand mill and sanded for 5h to obtain a precursor suspension;

[0054] The obtained precursor suspension is spray dried to obtain a precursor powder, which is then sintered at 500° C. for 10 h in an inert gas atmosphere to obtain a nitrogen-doped sodium iron phosphate pyrophosphate positive electrode material (i.e., the composite carbon source induced positive electrode material described in the technical solution of the present application), abbreviated as NFPP-N5.

[0055] Example 6

[0056] Weigh 211.457g NaH2PO4, 709.747g FePO4, 249.397g Na2CO3, 100g C6H10 08, 5g polyacrylonitrile was dissolved in 3L deionized water, stirred for 1h to mix evenly, and then added to a sand mill and sanded for 5h to obtain a precursor suspension;

[0057] The obtained precursor suspension is spray dried to obtain a precursor powder, which is then sintered at 500° C. for 10 h in an inert gas atmosphere to obtain a nitrogen-doped sodium iron phosphate pyrophosphate positive electrode material (i.e., the composite carbon source induced positive electrode material described in the technical solution of the present application), abbreviated as NFPP-N6.

[0058] Example 7

[0059] Weigh 211.457g NaH2PO4, 709.747g FePO4, 249.397g Na2CO3, 100g C6H 10 O8, 5g of diethylenetriaminepentaacetic acid was dissolved in 3L of deionized water, stirred for 1h to mix evenly, and then added to a sand mill and sanded for 5h to obtain a precursor suspension;

[0060] The obtained precursor suspension is spray dried to obtain a precursor powder, which is then sintered at 500° C. for 10 h in an inert gas atmosphere to obtain a nitrogen-doped sodium iron phosphate pyrophosphate positive electrode material (i.e., the composite carbon source induced positive electrode material described in the technical solution of the present application), abbreviated as NFPP-N7.

[0061] Example 8

[0062] Weigh 211.457g NaH2PO4, 709.747g FePO4, 249.397g Na2CO3, 100g C6H 10 O8, 5g melamine was added to 3L deionized water, stirred for 1h to mix evenly, and then added to a sand mill and sanded for 5h to obtain a precursor suspension;

[0063] The obtained precursor suspension is spray dried to obtain a precursor powder, which is then sintered at 500° C. for 10 h in an inert gas atmosphere to obtain a nitrogen-doped sodium iron phosphate pyrophosphate positive electrode material (i.e., the composite carbon source induced positive electrode material described in the technical solution of the present application), abbreviated as NFPP-N8.

[0064] Comparative Example 1

[0065] Weigh 211.457g NaH2PO4, 709.747g FePO4, 249.397g Na2CO3, 100g C6H 10 O8 was added to 3L of deionized water, stirred for 1h to mix well, and then added to a sand mill and sanded for 5h to obtain a precursor suspension;

[0066] The obtained precursor suspension was spray dried to obtain precursor powder, which was then sintered at 500° C. for 10 h under an inert gas atmosphere to obtain a positive electrode material, abbreviated as NFPP-1.

[0067] Comparative Example 2

[0068] Weigh 211.457g NaH2PO4, 709.747g FePO4, 249.397g Na2CO3, 100g C6H 10 O8, 5gC6H 12 O6 was added to 3L of deionized water, stirred for 1h to mix well, and then added to a sand mill and sanded for 5h to obtain a precursor suspension;

[0069] The obtained precursor suspension was spray dried to obtain precursor powder, which was then sintered at 500° C. for 10 h under an inert gas atmosphere to obtain a positive electrode material, abbreviated as NFPP-2.

[0070] The positive electrode materials prepared in the above-mentioned Examples 1 to 8 and Comparative Examples 1 to 2 are assembled into sodium ion batteries. The assembly steps of the sodium ion batteries all adopt standardized button battery assembly steps, and the steps are as follows: the positive electrode material, conductive carbon black (SuperP) and polyvinylidene fluoride (PVDF) prepared in the examples or comparative examples are weighed in a mass ratio of 8:1:1, and N-methylpyrrolidone (NMP) is used as a solvent. The mixture is ground into a uniform slurry in a ball mill, and then the slurry is evenly coated on an aluminum foil with an automatic coating machine, dried at 80°C for 12 hours under a vacuum environment, and then cut into pieces, and the pieces are used as the positive electrode; then a sodium sheet is used as a negative electrode, a glass fiber (Whatman GF / C) is used as a separator, and an electrolyte is 1M NaPF6 / EC:DMC (v:v=1:1). The CR2025 button battery is assembled in an argon atmosphere glove box with water and oxygen values ​​both lower than 0.01ppm.

[0071] The sodium ion batteries corresponding to Examples 1 to 8 and Comparative Examples 1 to 2 were subjected to a first cycle charge and discharge test. Table 1 shows the discharge specific capacity data of Examples 1 to 8 and Comparative Examples 1 to 2.

[0072] Figure 3 is the first cycle charge and discharge curve of the sodium ion battery corresponding to Example 3; Figure 3 As shown, the 0.2C first cycle discharge specific capacity reaches 102 mAh / g, and has a first efficiency of over 99%.

[0073] The sodium ion batteries corresponding to the positive electrode materials prepared in Examples 4 and 5 and Comparative Example 1 were tested for rate performance at 0.2C, 0.5C, 1C, 2C, 5C, 2C, 1C, 0.5C, and 0.2C, respectively. The test voltage window was 2.0 to 3.6V, and the test temperature was 25°C. The test results are as follows: Figure 4 As shown, it can be seen that after the introduction of the nitrogen-containing carbon source, the rate performance is significantly improved, indicating that the electronic conductivity is improved; under 5C conditions, both Example 4 and Example 5 have a reversible specific capacity of more than 85 mA h / g.

[0074] Figure 5 This is a long cycle data chart of the sodium ion battery corresponding to Example 6; we can see that after the introduction of the nitrogen-containing carbon source, the material still maintains very excellent structural stability, indicating that the introduction of the nitrogen-containing carbon source does not destroy the crystal structure of sodium iron pyrophosphate, but only plays the effect of carbon source coating.

[0075] Figure 6 This is the first cycle charge and discharge curve of Example 7; the 0.2C first cycle discharge specific capacity can reach 112.5 mAh / g, which is at the forefront of the current commercial sodium polyanion materials.

[0076] Figure 7 This is the first cycle charge and discharge curve of Example 8; the 0.2C first cycle discharge specific capacity can reach 120 mAh / g, which is at the forefront of the current commercial sodium polyanion materials.

[0077] Table 1

[0078] Sodium-ion batteries Second carbon source Specific capacity / mA·h·g-1 Example 1 Polyethyleneimine 102.44 Example 2 Polyacrylamide 105.20 Example 3 Polyamide 102.31 Example 4 Polyimide 104.19 Comparative Example 1 / 92.21 Example 5 Polyurea 102.77 Example 6 Polyacrylonitrile 101.52 Example 7 Diethylenetriaminepentaacetic acid 112.50 Example 8 Melamine 105.03 Comparative Example 2 <![CDATA[C6H 12 O6]]> 97.31

[0079] It can be seen from Examples 1 to 8 and Table 1 that the specific capacity of the positive electrode material prepared by the technical solution of the present application can reach more than 100 mAh / g, which has obvious advantages over the single carbon source in Comparative Example 1. It also has obvious advantages over Comparative Example 2 with dual carbon sources but without nitrogen source.

[0080] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A composite carbon source-induced cathode material, characterized in that: The invention is prepared from components including a sodium source, a phosphorus source, an iron source, a first carbon source and a second carbon source. The dosage of the sodium source, the phosphorus source and the iron source is adjusted so that the molar ratio of sodium, phosphorus and iron is in the range of 1-1.05:1:0.65-0.85; the total weight of the first carbon source and the second carbon source accounts for 20wt% of the total weight of the sodium source, the phosphorus source and the iron source; the weight ratio of the first carbon source to the second carbon source is 1-20:1; and the second carbon source is a nitrogen-containing organic matter.

2. The positive electrode material according to claim 1, characterized in that The sodium source is one or more of disodium hydrogen phosphate, sodium dihydrogen phosphate, sodium phosphate, sodium carbonate, sodium bicarbonate, sodium pyrophosphate, sodium oxalate, and sodium acetate; And / or, the iron source is one or more of ferric nitrate, ferric phosphate, ferrous oxalate, ferric oxide, ferrosiric oxide, ferrous acetate, and ferric acetylacetonate; And / or, the phosphorus source is one or more of sodium dihydrogen phosphate, disodium hydrogen phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, sodium phosphate, sodium pyrophosphate, and phosphoric acid; and / or, the carbon source is one or more of citric acid, ascorbic acid, oxalic acid, stearic acid, glucose, agarose, sucrose, and cellulose; And / or, the second carbon source is one or more of polyethyleneimine, polyacrylamide, polyamide, polyimide, polyurea, polyacrylonitrile, melamine, and diethylenetriaminepentaacetic acid.

3. The positive electrode material according to claim 1, characterized in that The solid content is 5 to 50 wt%.

4. A method for preparing the positive electrode material according to claim 1, characterized in that: The following steps are involved: S1. Weigh the sodium source, phosphorus source, first carbon source, second carbon source and iron source respectively, add them into deionized water in sequence, stir and disperse to obtain a suspension; S2, performing sand milling and nano-processing on the suspension prepared in S1, and then spray drying the suspension to obtain a precursor powder; S3. The precursor powder prepared in S2 is sintered in an inert atmosphere to obtain a composite carbon source-induced positive electrode material.

5. The preparation method according to claim 4, characterized in that: In S1, the stirring method is one of mechanical stirring and magnetic stirring; the stirring speed is 100-1200 rpm; the stirring temperature is 10-60° C.; and the stirring time is 1-10 h.

6. The preparation method according to claim 4, characterized in that: In S2, the sanding speed is 2000 rpm; the sanding temperature is 20° C.; and the D50 of the solid particles after sanding is less than 100 nm.

7. The preparation method according to claim 4, characterized in that: In S2, the inlet temperature of the spray drying is 260°C, the outlet temperature is 110°C, the fan speed is 90%, and the peristaltic pump speed is 40%.

8. The preparation method according to claim 4, characterized in that: In S3, the inert atmosphere is one of argon, nitrogen, and hydrogen-argon mixed gas; the sintering temperature is 500-600° C., the heating rate is 1-5° C. / min, and the sintering time is 10-15 h.

9. An electrode sheet, characterized in that: The positive electrode material is prepared by inducing the composite carbon source described in claim 1.

10. Use of the composite carbon source-induced positive electrode material according to claim 1 in the field of sodium ion batteries.